THE EFFECT OF REGIONAL TAX REVENUE AND REGIONAL RETRIBUTION ON INCREASING REGIONAL ORIGINAL INCOME (A Case Study at the Seruyan District Financial and Asset Management Revenue Service) - Iswanti, Iswanti (Program Doktor Ilmu Ekonomi, 2021)
The purpose of this study is to find out how much the amount ofRegional Taxes, Regional Levies and Regional Original Revenue (PAD)of Seruyan Regency in 2015-2019, as well as knowing the effect ofRegional Taxes and Regional Levies on Regional Original Income (PAD)both simultaneously and partially. The population in this study is theSeruyan Regency APBD Realization Report for the 2015-2019 fiscal year.The sample technique used in this research is judgment sampling. Theanalysis technique used in this research is descriptive statistical analysisand multiple regression. Based on the data analysis, information isobtained that the amount of Original Regional Revenue in 2015, 2016 and2019 has decreased, while in 2017 and 2018, Regional Original Incomehas increased, this indicates that the original Regional Revenue data isgrouped or does not vary.Keywords: Local Taxes, Regional Retributions, Local Revenue